Strategic analysis of the forest productive chain in the region of the Monarch Butterfly Biosphere Reserve - Rodríguez Zúñiga, Joel; González Guillén, Manuel de Jesús; Valtierra Pacheco, Esteban (Instituto de Ecología, A.C., 2018)
In the Monarch Butterfly Biosphere Reserve there is delinking of the forest productive chain. The objective of this study was to apply the strategic analysis to the forestry production chain in three community forest enterprises in the Monarch Butterfly Biosphere Reserve, in order to understand the production process and to establish better options for integration, as well as to identify factors that enhance their effectiveness and efficiency. Strategic analysis is a methodology that is built with a strategic vision according to the needs of the phenomenon under study. If the community forest enterprises partially completes the first link and wants to consolidate it, it will need to strengthen it in terms of its organizational culture or corporate principles. Integrating more links, it will be achieved through an analysis of the causes of the current state and of the competitive advantages of the product in the market. The degree of integration of the community forest enterprises allows members to perform more activities in the links of production, maintenance, protection, supply and processing, and it represents greater social organization and a culture of rational exploitation and conservation of forest resources. More than half of the members perceive that profits from forestry represent less than 25% of their economic system; however, this could increase based on the integration of the forestry production chain.